Physiological and anatomical basis of differential tolerance to soil flooding of Lotus corniculatus L. and Lotus glaber Mill - Striker, G.G; Insausti, P; Grimoldi, A.A; Ploschuk, E.L; Vasellati, V (Plant and soil, 2005)
Lotus corniculatus L. and Lotus glaber Mill, are warm-season legume species adapted to many kinds of environmental stress, including flooding conditions, whereas other popular forage legumes, like alfalfa or white clover, cannot thrive. This study evaluates the relationship between root aerenchyma, water relations and leaf gas exchange and the differential tolerance to soil flooding of L. corniculatus and L. glaber. Adult plants of these species, established independently in grasslands mesocosms, were subjected to 40 days of early spring flooding at a water depth of 6 cm. Both species presented constitutive aerenchyma tissue in the roots. Under flooding conditions, this parameter was 26.2% in L. glaber and 15.3% in L. corniculatus. In addition, flooded plants of L. glaber presented a leaf biomass 47.5% higher above water while L. corniculatus showed a leaf biomass 59.6% lower in the same layer, in comparison to control plants. Flooded plants of L. glaber maintained the stomatal conductance (gs) and transpiration rate (E) for 25 days, although these parameters reduce slightly to 40—60% in comparison to controls after 40 days of flooding. In this species, a reduction in photosynthesis (A) in flooding conditions was detected only on the last day of measurement. In L. corniculatus, the same parameters (gs, E and A) were affected by flooding since day 18 of treatment, and values reached 25—40% in comparison to control plants after 40 days of flooding. Flooding did not affect above-ground biomass in L. glaber; while in L. corniculatus,, above-ground biomass was 35% lower than in control plants. Our results confirmed that L. glaber is more able to cope with flooding stress than L. corniculatus, even in the presence of natural competitors. On the whole, this experiment provides information that can aid in the identification of anatomical and physiological parameters associated with flood-tolerance in this forage legume species, with economic potential for the agricultural areas subject to periodic flooding.